A blowfly-derived dna approach to assess diversity of tropical mammals / Lee Ping Shin - Lee, Ping Shin (2016)
Most tropical mammal species are threatened or data-deficient. Data collection is impeded by traditional monitoring approaches which can be laborious, expensive and struggle to detect cryptic diversity. Monitoring approaches using mammal DNA derived from invertebrates, in particular blowfly-derived DNA, have recently been suggested as alternatives to traditional field methods. As a step towards development of blowfly-derived DNA as an effective method for mammal monitoring in Peninsular Malaysia, my research objectives are: (i) to determine the persistence period of amplifiable mammal mtDNA in blowfly guts; (ii) to design and test primers that can selectively amplify mammal COI DNA mini-barcodes in the presence of high concentrations of blowfly DNA; (iii) to determine the dispersal range of blowflies in forests; (iv) to calibrate the performance of blowfly-derived mammal DNA at generating species inventories and richness estimates against traditional methods: cage trapping, mist netting, hair trapping and scat collection in the field; (v) to calibrate the performance of blowfly-derived DNA at generating species inventories and richness estimates against the most popular method to assess megafaunal diversity - camera trapping in the field. The persistence period of amplifiable mammal DNA in blowfly guts was in the range of 24 h to 96 h post-feeding indicating the need for retrieving flies within 24 h of capture to detect mammal mtDNA in sufficient quantity and quality. A short (205 bp) mammal COI DNA mini-barcode, suitable for high-throughput sequencing, could distinguish most mammal species (including separating dark taxa). The daily dispersal range of Chrysomya spp. blowflies suggests that individuals contributing blowfly-derived DNA would have been within 3 km the location where blowflies were collected over 24 h period. The field study in Ulu Gombak Forest Reserve that calibrated the performance of blowfly-derived mammal DNA against traditional methods (cage traps, mist nets, hair traps, and scat collection) over 1,440 trap days revealed that blowfly traps and mist nets detected the joint highest number of wild mammal species (6 species), and only one species was detected by multiple methods. Compared to traditional field methods, blowfly-derived DNA detected both volant and non-volant species from wider body size ranges. In Tembat Forest Reserve with megafauna, calibration of blowfly-derived DNA against camera traps, the most popular method in megafaunal diversity assessment, blowfly-derived DNA detected more species (n=11) than camera traps (n=9) across 1,200 trap days, with only one species detected by both methods. With further calibration, blowfly-derived DNA may join the list of traditional field methods.